Adsorption Isotherms of Hydrogen on Granular Activated Carbon Derived From Coal and Derived From Coconut Shell. Issue 4 (4th March 2017) - Nasruddin,; Martin, Awaludin; Alhamid, Muhammad Idrus; Tampubolon, Daniel
ABSTRACT: The development of adsorption-based storage systems requires a basic understanding of the isotherms over a wide range of pressure and temperatures for various types of adsorbents. This research is to generate experimental isothermal adsorption data for the adsorption of hydrogen gas on activated carbon. The adsorption apparatus is based on a volumetric method, and the experiments were conducted at temperatures ranging from 273 to 308 K and pressures up to 4 MPa. Two types of activated carbon, (i) a granular coal from Indonesia and (ii) a coconut-shell activated carbon that is produced in the laboratory, were used in the experiments. The experimental data are analyzed using the Langmuir, Toth, and Langmuir–Freundlich isotherm models.